INGLIZ TILI FANINI O‘QITISHDA UCHRAYDIGAN TURLI MUAMMOLAR VA YECHIMLAR. - Eshtayeva Dildora Kaxarovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article examines the diversity of contemporary teaching methods in English language education, which considers the integration of technology, student-centered approaches, communicative language teaching strategies, project-based learning, multimodal resources, and cultural competence in the pursuit of transformative learning.